Teaching distance relay using matlab/simulink graphical user interface - Muhd Hafizi, Idris; Mohd Zamri, Hasan; Surya, Hardi (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.